PENGARUH MOTIVASI BELAJAR DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS IX DI SMP NEGERI 1 SIANTAR 2023/2024 - Jan Simon Silitonga; Binsar Tison Gultom; Anton Luvi Siahaan (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to determine the effect of learning motivation and learning discipline on the learning achievement of ninth grade students at SMP Negeri 1 Siantar. The variables in this study are learning motivation and learning discipline as independent variables and learning achievement as the dependent variable. This type of research is quantitative research with a quantitative descriptive data analysis approach, with a research population of all 9th grade students of SMP Negeri 1 Siantar and a research sample of IX-3 and IX-2 students of SMP Negeri 1 Siantar consisting of 53 students selected using Simple random sampling (Slovin formula). Data collection techniques using instruments: (1) learning motivation questionnaire, (2) discipline questionnaire, and (3) learning achievement in the form of Economics daily test scores.The results of this study indicate that: (1) there is a positive and significant effect of learning motivation on learning achievement, this result can be seen in the t test where the tcount value of learning motivation (3.374)> ttable value (1.67528) which means that the variable is significant. (2) there is a positive and significant effect of learning discipline on learning achievement, this result can be seen in the t test where the tcount value of learning discipline (3.272)> ttable value (1.67528) which means that the variable is significant. (3) learning motivation and learning discipline together affect learning achievement, this result can be seen in the F test where the Fcount value (6.600) > than the Ftable value (2.79). The RSquare coefficient of determination test is known to be 0.216, which means that 21.6% of the learning motivation and learning discipline variables affect the learning achievement of class IX students at SMP negeri 1 Siantar and the remaining 78.4% is the influence of other variables not examined in this study.